STRATEGI MENUMBUHKAN NILAI-NILAI PENDIDIKAN ISLAM BAGI REMAJA (STUDI KASUS MAJLIS RAUDHATUL HIDAYAH FISABILILLAH EMPANG BOGOR) - Muhammad Adista; Rafsan Rafsan; Ayu Ratih Rizki Pradika (Jurnal Cendekia Ihya, 2025)
Adolescents are in a phase of identity discovery that is vulnerable to social and technological influences, so the process of internalizing Islamic educational values ​​faces various challenges. This study aims to describe the forms of activities, inhibiting factors, and strategies for instilling Islamic educational values ​​for adolescents at the Majlis Raudhatul Hidayah Fisabilillah Empang Bogor. This study uses a qualitative case study approach with data collection techniques through interviews, observation, and documentation of two teachers and ten members of the majlis as research subjects. The results show that the instillation of Islamic educational values ​​includes the values ​​of faith, worship, and morals, which are instilled through habits, role models, counseling, and competent parenting. Inhibiting factors in the process of instilling values ​​include a lack of discipline and the emergence of laziness among adolescents. Strategies implemented to overcome these obstacles are strengthening positive habits, increasing teacher role models, expanding counseling activities, and establishing effective communication between caregivers and congregations. This study contributes to the development of a model for developing adolescent character development based on Islamic values ​​in non-formal educational institutions.